A novel image steganography technique based on quantum substitution boxes. (August 2019) - Abd EL-Latif, Ahmed A.; Abd-El-Atty, Bassem; Venegas-Andraca, Salvador E.
Highlights: Two contributions for secure data hiding have been made in this paper. Non-linear properties of quantum walks is utilized to construct S-boxes. An efficient steganography technique is proposed. It is able to resist the probable attacks of the quantum computer. Results show that it has favorable performance and high security. Abstract: Substitution boxes play an essential role in designing secure cryptosystems. With the evolution of quantum technologies, current data security mechanisms may be broken due to their construction based on mathematical computation. Quantum walks, a universal quantum computational model, play an essential role in designing quantum algorithms. We utilize the benefits of quantum walks to present a novel technique for constructing substitution boxes (S-boxes) based on quantum walks (QWs). The performance of the presented QWs S-box technique is evaluated by S-box evaluation criteria, and our results prove that the constructed S-box has vital qualities for viable applications in security purposes. Furthermore, a new technique for image steganography is constructed. The proposed technique is an integrated mechanism between classical data hiding and quantum walks to achieve better security for the embedded data. The embedding and extraction procedures are controlled by QWs S-box. The inclusion of cryptographic QWs S-box ensures the security of both embedding and extraction phases. At the extraction phase, only the stego image and the secret values are needed for constructing the secret data. Experimental results demonstrate that the presented technique has a high-security, high embedding capacity and good visual quality.